Bi-directional Beams Waveguide Slotted Antenna at Millimeter Wave - Muataz W. Sabri; Noor A. Murad; Mohammed K.A. Rahim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper focused on designing a bi-directional beams waveguide slotted antenna at millimetre wave spectrum. Waveguide slotted antenna is known for its highly directional pattern. By having bi-directional pattern, the capacity of system coverage can be expanded. The design is implemented by using antenna slot theory on a waveguide structure. The slotted are made on two wall surfaces and the performance is compared to the slotted on single wall. The two models designs are simulated using Computer Simulation Technology (CST) microwave software. The simulation results show that both models operate at 30 GHz with minimum reflection coefficient of -24.63 and -25.01 dB respectively. The two models achieved a fair high gain at 15.5 dB and 13.3 dB with directional beamwidth of 8.9 degree. The proposed bi-directional beams structure achieved a comparable gain in both directions when compared to the single direction.